The Weber equations and the corresponding Ertel theorem for a general rotating fluid - B. S. C. Saint-Guily (Meteorologische Zeitschrift, 1995)
The case of a rotating non isentropic fluid is considered. The dynamical equations are written in Lagrangian form to arrive at the Weber transformation and equations in terms of the Hamilton function and the entropy. Then is obtained an extension of the Ertel and Rossby conservation theorem. Although these results are not new, the derivation remains quite near Ertel's way.